PENGARUH BIAYA OPERASIONAL TERHADAP PRODUKTIVITAS TENAGA KERJA DI KJPP HERMAN MEIRIZKI SURABAYA - Winda Kartika; Imas Dian Oktarini (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2022)
Labour productivity is measure of the succea of a company. This is inseparable from the operational cost incurred to support business activities. The research objective is to determine the magnitude of the effect of operational costs on labor productivity. This study collects data through primary data and secondary data from financial data in 2020. Hypothesis testing is carried out in this study using simple linear regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis testing t test. Where the conclusion of this study shows the correlation coefficient between costs. operational with labor productivity amounting to 0.995 and the results of the test tcount (13.738)> t table (2.919) at 95% confidence level with 0.005 significance. The conclusion of this research is that Ho is rejected and Ha is accepted, meaning that operational costs have a significant effect on productivity by 99% and 1% is another factor